2002
DOI: 10.1080/01919510208901636
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Radicals using Discharge inside Bubbles in Water for Water Treatment

Abstract: A new method for a water treatment utilizing radicals produced by a discharge inside bubbles in water is proposed. Radicals with short lifetime (atomic oxygen and OH radical) are used effectively for the water purification because those are generated by discharge inside bubbles in water. OH radical production was confirmed by ;a light emission of the discharge using the spectroscopic technique. Dissolved ozone concentration of about 0.3 mg/l was obtained when oxygen was used as a bubbling gas. Decolorization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…The majority of such studies that have been reported so far used streamer discharges in water, which are generated by the application of high voltage pulses with thin needle-like electrodes. [1][2][3][4] High energy electrons, free radicals, ultraviolet (UV) radiation, ozone, and shock waves generated by such discharges are used for water purification. 5,6) For example, in industrial applications, disinfection by ozone that are generated in the gas phase by corona discharges is widely used for water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of such studies that have been reported so far used streamer discharges in water, which are generated by the application of high voltage pulses with thin needle-like electrodes. [1][2][3][4] High energy electrons, free radicals, ultraviolet (UV) radiation, ozone, and shock waves generated by such discharges are used for water purification. 5,6) For example, in industrial applications, disinfection by ozone that are generated in the gas phase by corona discharges is widely used for water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous phase ozone and H 2 O 2 concentration reached 0.774 mg/L and 11.993 mg/L respectively for a 60kV applied voltage. Compared with other studies [6], these concentrations tend to be much higher.…”
Section: Active Species Formedmentioning
confidence: 62%
“…The discharge systems are often very similar to the ones described in Section 3.1 without bubbles. For a plate-to-plate configuration, pulsed streamer discharge mostly occurred inside bubbles adjacent to the electrodes [97].…”
Section: Bubble Discharge Reactorsmentioning
confidence: 99%